Development of Web-Based Interactive Learning Multimedia with Contextual Approach to Facilitate Mathematical Critical Thinking Ability - Nurhayati, Rini; Waluya, St. Budi; Noor Asih, Tri Sri (Unnes Journal of Mathematics Education Research, 2021)
Digital learning resources were indispensable in today's mathematics learning, both offline and online, to support abstract mathematical concepts and train critical thinking skills. This research was intended to produce web-based learning multimedia products with a contextual approach using Adobe Flash CS6 software to facilitate XI grade high school students' critical thinking skills and determine its feasibility. The research method was research and development (RnD) using the ADDIE (analysis, design, development, implementation, evaluation) model. The validation results of multimedia development products by material experts and media experts meet the valid criteria with an average score of 4.09. The practicality test by two teachers and six students showed an average score of 4.48 and was categorized as very practical. Evaluation of the practicality of implementing multimedia products found that the average critical thinking ability of students had exceeded the minimum completion limit, namely 64, and exceeded 75% of the number of students. The average difference test and the comparative proportion test showed that the students' critical thinking ability in the experimental class was better than in the control class. The results of this multimedia development could be feasible as a learning media because it meets the criteria of being valid, practical, and effective. Students' critical thinking skills increased after using multimedia with an average gain of 0.47. Web-based interactive multimedia learning is effective in facilitating students' critical thinking skills. Digital learning resources are indispensable in today's mathematics learning which can be combined offline and online to support abstract mathematical concepts and train critical thinking skills. This research is intended to produce web-based learning multimedia products with a contextual approach using Adobe Flash CS6 software to facilitate XI grade high school students' critical thinking skills and determine its feasibility. The research method was research and development (RnD) using the ADDIE (analysis, design, development, implementation, evaluation) model. The validation results of multimedia development products by material experts and media experts meet the valid criteria with an average score of 4.09. The practicality test by two teachers and six students showed an average score of 4.48 and was categorized as very practical. Evaluation of the practicality of implementing multimedia products found that the average critical thinking ability of students had exceeded the minimum completion limit, namely 64, and exceeded 75% of the number of students. The average difference test and the comparative proportion test showed that the students' critical thinking ability in the experimental class was better than in the control class. This multimedia development product could be feasible as a learning media because it meets the criteria of being valid, practical, and effective. Students' critical thinking skills increased after using multimedia with an average gain of 0.47. This multimedia can be used as an online learning resource and can be accessed via a computer or smartphone browser.